How Does Pre-Service Teachers’ Self-Efficacy Relate to the Fulfilment of Basic Psychological Needs During Teaching Practicum? - Denise Depping; Timo Ehmke; Michael Besser; Dominik Leiß (Education Sciences)
The aim of this study was to investigate environmental conditions in teaching practicums that support the development of pre-service teachers’ self-efficacy beliefs. Motivational orientations such as self-efficacy beliefs and enthusiasm are crucial aspects of professional teacher competence and thus should be fostered right from the beginning of teacher training. Against the backdrop of self-determination theory, which is connected to intrinsic motivation, we examined effects from the fulfilment of basic psychological needs (needs for competence, autonomy and relatedness) during teaching practicums on changes in levels of perceived self-efficacy. A total of 103 German pre-service teachers enrolled in a Bachelor’s or Master’s Degree Program participated in this study at two times of measurement. The results reveal that the fulfilment of basic psychological needs and especially a sense of relatedness contributed positively to gains in self-efficacy. The findings are discussed with regard to the design of practicums in teacher training.